Islamic Apologetics and the Commodification of Religion in the Digital Public Space - Mukhroman, Iman; Muhtadi, Asep Saeful; Mukarom, Zaenal; Turmudi, Hamzah (Jurnal Iman dan Spiritualitas, 2026)
Insights on the digital transformation of Islamic preaching in Indonesia, for example, highlight how religious practice gets enmeshed with social media's symbolic economy. In this paper, I examine the transition from da’wah to digital commodity in Islamic apologetics through the channel Bang Zuma Official on YouTube, and how faith, authority, and algorithms intersect in the digital public sphere. This study adopts a qualitative interpretive method, building on the analytics of Robert Entman’s (1993) framing analysis and Vincent Mosco’s (2009) theory of media commodification. The main data are collected from the video “Penyesat Itu Bergelar Yesus Kristus.. Siapa Pengikutnya???”(published March 6, 2025). They are, meaning structure or ideological representation, and the forms of commodification of religion in Bang Zuma’s apologetic discourse. The results indicate that Bang Zuma conceptualizes Islam as the ultimate truth and other religions in terms of epistemological distortions. His rhetorical style connects theological argumentation with digital aesthetics, rendering da’wah an ideological spectacle. Three forms of commodification are identified: content (theological messages simplified for viral status), audience (those who consume or engage via donations act out digital fatigue and labour), and indeed the preachers themselves as spiritual labour modified in relation to algorithmic concerns.